2010
DOI: 10.1002/cncr.25799
|View full text |Cite
|
Sign up to set email alerts
|

Additive effect on survival of Raf kinase inhibitor protein and signal transducer and activator of transcription 3 in high‐grade glioma

Abstract: BACKGROUND:Animal studies have shown cooperative contribution of the Ras/Raf/MAPK and PI3K/Akt/mTOR signaling pathways in glioblastoma formation. However, this joint action has not yet been confirmed in human studies. METHODS: The expression of Raf kinase inhibitory protein (RKIP) was examined in 159 patients with high-grade and low-grade gliomas and correlated with previously obtained data on the activation of signal transducer and activator of transcription 3 (STAT3), a downstream effector of the PI3K/Akt/mT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 38 publications
0
25
2
Order By: Relevance
“…In human breast carcinoma and metastatic colorectal carcinoma, RKIP expression is lost in lymph node metastases but not in primary tumours 18–20. In several solid tumours, loss of cytoplasmic RKIP has also been associated with poor prognosis such as in prostate, colorectal, gastrointestinal stromal tumours, gastric adenocarcinoma of the intestinal subtype, high grade gliomas, hepatocellular carcinoma and pancreatic ductal adenocarcinoma 19 23 24 28 32 33. By contrast, many studies, including ours, have shown the absence of RKIP in primary tumours independently of associations with the presence of tumour aggressiveness and metastasis 21 22 26 29–31 45 46.…”
Section: Discussionmentioning
confidence: 59%
“…In human breast carcinoma and metastatic colorectal carcinoma, RKIP expression is lost in lymph node metastases but not in primary tumours 18–20. In several solid tumours, loss of cytoplasmic RKIP has also been associated with poor prognosis such as in prostate, colorectal, gastrointestinal stromal tumours, gastric adenocarcinoma of the intestinal subtype, high grade gliomas, hepatocellular carcinoma and pancreatic ductal adenocarcinoma 19 23 24 28 32 33. By contrast, many studies, including ours, have shown the absence of RKIP in primary tumours independently of associations with the presence of tumour aggressiveness and metastasis 21 22 26 29–31 45 46.…”
Section: Discussionmentioning
confidence: 59%
“…The decreased expression of PTEN (at RNA or protein levels), or loss of heterozygosity of chromosome 10q, which encompasses the PTEN gene, were reported as indicators of shorter GBM patient survival [97]; however, this is still controversial [98]. Another recent example is the prognostic value of RAF kinase inhibitor, the expression of which was reported to associate with longer overall survival of GBM patients [99]. In the future, novel studies aiming to understand how the integrated analysis of several molecular components of growth signaling pathways may help clarify the true prognostic value of these biomarkers and lead to their integration into the clinical management of GBM patients.…”
Section: Growth Factor Signaling Pathwaysmentioning
confidence: 96%
“…77 A third clinical study showed that overall survival was best for high-grade gliomas that are positive for RKIP and negative for STAT3 (signal transducer and activator of transcription 3) expression. 78 However, in another report, Martinho et al found that only a small proportion (i.e., approximately 10%) of gliomas from human patients are associated with loss of RKIP expression. 79 Evidence from in vitro experiments using human glioma cell lines is consistent with a role of RKIP as a metastasis suppressor, since RKIP inhibition promotes cell migration, whereas its overexpression suppresses glioma cell invasion.…”
Section: Rkip and Association With Brain Cancermentioning
confidence: 95%